AI 엣지 디바이스를 이용한 스마트 팩토리 시스템 설계 - 한성일(Seong-Il Han); 이대식(Dae-Sik Lee); 한지환(Ji-Hwan Han); 신한재(Han Jae Shin) (한국정보전자통신기술학회 논문지, 2022)
In this paper, we design a smart factory risk improvement system and risk improvement method using AI edge devices. The smart factory risk improvement system collects, analyzes, prevents, and promptly responds to the worker's work performance process in the smart factory using AI edge devices, and can reduce the risk that may occur during work with improving the defect rate when workers perfom jobs. In particular, based on worker image information, worker biometric information, equipment operation information, and quality information of manufactured products, it is possible to set an abnormal risk condition, and it is possible to improve the risk so that the work is efficient and for the accurate performance. In addition, all data collected from cameras and IoT sensors inside the smart factory are processed by the AI edge device instead of all data being sent to the cloud, and only necessary data can be transmitted to the cloud, so the processing speed is fast and it has the advantage that security problems are low. Additionally, the use of AI edge devices has the advantage of reducing of data communication costs and the costs of data transmission bandwidth acquisition due to decrease of the amount of data transmission to the cloud. 본 논문에서는 AI 엣지 디바이스를 이용한 스마트 팩토리 위험도 개선시스템 및 위험도 개선방법을 설계한다. 스마트 팩토리 위험도 개선시스템은 AI 엣지 디바이스를 이용하여 스마트 팩토리에서 작업자의 작업수행 과정을 수집, 분석, 예방 및 신속 대처하고, 작업자의 작업 수행시 불량률을 개선하면서 작업시 발생 가능한 위험을 저감할 수 있다. 특히 작업자 이미지 정보, 작업자 생체정보, 장비 구동 정보 및 제조된 제품의 품질정보에 기초하여 위험도 이상 조건을 설정할 수 있고, 효율적이고 정확도 높은 작업이 되도록 위험도 개선이 가능하다. 또한 스마트 팩토리 내부의 카메라 및 IoT 센서 등에서 수집된 데이터는 모두 클라우드로 보내지 않고 AI 엣지 디바이스에서 처리하고, 필요한 데이터만 클라우드 등으로 전송할 수 있으므로 처리 속도가 빠르고, 보안에 관한 문제가 적다는 장점이 있다. 추가적으로 AI 엣지 디바이스를 사용함으로써 클라우드로 데이터 전송량이 감소하여 데이터 통신비 및 데이터 전송 대역폭을 확보하는 비용이 절감되는 장점이 있다.